Strategic Alliances and Technological Innovation: Conditions and Mechanisms - Darko Zupanc; Klavdij Logožar (Naše gospodarstvo/Our economy, 2026)
This paper examines how strategic alliances enable firms to access new technologies and enhance innovation performance, and under which conditions such alliances succeed or fail. The study presents a structured conceptual synthesis of peer-reviewed literature on strategic alliances and technological innovation, integrating multiple theoretical perspectives and evidence from technology-intensive industries. It identifies key mechanisms – such as knowledge transfer, learning processes, and alliance governance – through which strategic alliances influence innovation outcomes. The analysis shows that strategic alliances can significantly enhance innovation outcomes when partners demonstrate strong technological complementarity, effective governance structures, and high absorptive capacity. Conversely, misaligned objectives, weak governance, and risks of knowledge leakage often undermine alliance performance. The study is conceptual and does not empirically test causal relationships. The findings provide guidance for managers designing technology-oriented alliances and for scholars developing more nuanced models of collaborative innovation. The paper contributes by synthesising fragmented literature into an integrated framework that highlights the conditions for success and failure in alliance-based innovation strategies.